Menganalisis Implementasi Profil Pelajar Pancasila di SMA Negeri 2 Palembang: Analyzing the Implementation of Pancasila Student Profiles at SMA Negeri 2 Palembang - Nur Fitri Aisyah; Effendi Nawawi (LPPM Institut Studi Islam Sunan Doe, 2022)
The world of education teaches many things to humans regarding human nature and background both in terms of identity, social, mental state, religion, and others. Educators, students, expert staff, and education providers are objects and subjects that form a culture that lives in the midst of the educational process. Pancasila values are needed in the learning process so that they can be instilled in students. The purpose of this study was to describe the teacher's efforts in implementing Pancasila student profiles for students at SMA Negeri 2 Palembang. This study uses a qualitative method. Based on the results of the research, it is known that the efforts that have been made by teachers/educators at SMA Negeri 2 Palembang in instilling Pancasila values are by using the Pancasila Student Profile Strengthening Project. The theme raised by teachers/educators at SMA Negeri 2 Palembang is a Sustainable Lifestyle with the sub-theme of Waste Management. The elements of achievement that this project aims to achieve are taking care of the environment, collaborating, analyzing and evaluating reasoning and coming up with original compositions and actions.